Efektivitas Program Sekolah terhadap Pendidikan Pra Baligh pada Peserta Didik Kelas VI Sekolah Dasar Islam Terpadu Al-Hikmah - Anisa Dwi Pratiwi; Bambang Irawan (Departement of Mathematics Education, 2023)
Based on observations at the Al-Hikmah Integrated Islamic Elementary School, the pre-adulthood period causes students to become less self-confident and do not know what obligations they have if they have experienced the pre-baligh period. Therefore, schools have an important role in providing guidance to students. The aim of this research is to find out how effective school programs are in pre-adult education. This research method is a survey type quantitative research method. The sampling technique uses random sampling with data collection techniques using questionnaire instruments and documentation. Data analysis used a simple linear regression test formula with the results of school program research on pre-majority education showing an effectiveness value of 32.9%.